Piperine-loaded mesoporous silica nanoparticles as a promising strategy for targeting Echinococcus granulosus protoscoleces - Keivan Sahebi; Sara Takallu; Hassan Foroozand; Mobina Amirsoleymani; Seyed Mahmoud Sadjjadi; Yosef Sharifi; Rasoul Alimi; Zahra Zareshahrabadi; Esmaeil Mirzaei; Aref Teimouri (Scientific Reports)
Abstract Medical and surgical treatments for cystic echinococcosis (CE) are challenged by various complications. This study evaluates in vitro protoscolicidal activity of piperine-loaded mesoporous silica nanoparticles (PIP-MSNs) against protoscoleces of Echinococcus granulosus. MSNs were prepared by adding tetraethyl orthosilicate to cetyltrimethylammonium bromide and NaOH, and then loaded with PIP. The mean particle size and hydrodynamic diameter of MSNs were determined at 68 ± 4.5 and 101.4 ± 50.4 nm using transmission electron microscopy and dynamic light scattering, respectively. X-ray diffraction, Fourier-transform infrared analysis, and UV-spectrophotometry confirmed drug loading. Drug loading efficiency and drug loading capacity were calculated at 60% and 18%, respectively. The drug release profile confirmed a 75% PIP release plateau after about 24 h. The cytotoxicity assay showed cell viability > 90% in all concentrations used (≤ 512 µg/mL). E. granulosus protoscoleces were exposed to PIP-MSNs and their viability was assessed using the eosin exclusion test. In a dose-dependent manner (p < 0.001), exposure to 375 and 500 µg/mL of PIP-MSNs for 180 min killed 89.67 and 94.67% of protoscoleces, respectively. This study introduces PIP-MSNs as a potential protoscolicidal agent in the treatment of CE. Further studies are necessary to uncover safety aspects, biodistribution patterns, and potential combination therapies.